Observational Cross Sectional Study on Blood Donors .....................................................IJMTFM (2011) 1(2):65-69 - G.M., Raju; Vijayanath, V; M.R., Anitha (International Journal of Medical Toxicology and Forensic Medicine, 2012)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --><!--[endif] -->Background: This study was conducted to document the frequency ABO & rhesus blood groups in potential male blood donor belong to south area of Karnataka. Methods: The data of blood donors from July 2009 to December 2009. Results: Total number of donors studied was 3048. The commonest blood group was O present in 37.87% followed by B in 29.98%, A in 23.88% and AB in 8.29%. While 95.41% donors were Rh positive and 4.59% was Rh negative. The maximum donors were between in age group 20-39 years. The maximum prevalence of Hemoglobin % ranges from 13.0-13.9 about 2983(75.11%). The maximum prevalence of weight among the donors was between 60 to 69Kgs about 1201(39.40%) and the least weight appears between 80 to 90Kgs about 254(8.4%). Conclusion: Blood group O is the commonest ABO blood group and 95.41% are Rh + in this area, the maximum prevalence of donors in age group, Hb% and Weight are 20.39 yrs, 13.0-13.5 gm% and 50-69 Kgs respectively. Key Words: ABO blood group, Rhesus blood group, Prevalence of age group, weight and Hb% in blood donors.